2010
DOI: 10.1111/j.1600-0846.2010.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing adherence to dermatology treatments: a review of self-report and electronic measures

Abstract: While several self-report measures of adherence have been validated in chronic disease populations, their relevance in dermatology patients has not been studied. A dermatology-specific instrument for the measurement of adherence would contribute to improved outcomes; until such a tool exists, researchers and clinicians should consider nonadherence as a possible factor in skin disease that is not responsive to treatment. Electronic monitoring provides the most reliable means of measuring adherence, and may prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 37 publications
0
24
0
2
Order By: Relevance
“…58 Measuring adherence is challenging because traditional methods of patient self-report tend to overestimate adherence. 52,59 Electronic monitoring devices can improve objective adherence assessment, but not all topical medications are compatible for use with electronically monitored containers, and these containers have not been widely studied in dermatology. 52,59 Electronically monitored adherence for 3 different skin conditions demonstrated that adherence was highest on days near the time of a scheduled office visit.…”
Section: Adherence To Treatment Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Measuring adherence is challenging because traditional methods of patient self-report tend to overestimate adherence. 52,59 Electronic monitoring devices can improve objective adherence assessment, but not all topical medications are compatible for use with electronically monitored containers, and these containers have not been widely studied in dermatology. 52,59 Electronically monitored adherence for 3 different skin conditions demonstrated that adherence was highest on days near the time of a scheduled office visit.…”
Section: Adherence To Treatment Regimensmentioning
confidence: 99%
“…52,59 Electronic monitoring devices can improve objective adherence assessment, but not all topical medications are compatible for use with electronically monitored containers, and these containers have not been widely studied in dermatology. 52,59 Electronically monitored adherence for 3 different skin conditions demonstrated that adherence was highest on days near the time of a scheduled office visit. 60 This suggested that when patients knew they would see their doctor soon, they were significantly more likely to use their medicine as directed.…”
Section: Adherence To Treatment Regimensmentioning
confidence: 99%
“…Count-based measures ask respondents to report the number of medication doses missed or taken in a certain interval, whereas estimation measures ask respondents to characterize their overall degree of regimen execution in terms of ratings or visual analog scales. The number of items on self-report adherence measures varies from single-item questions to more elaborate multi-item scales [1,5,45]. The number of items often reflects the degree to which the measure is seeking to capture a variety of adherence-related factors, such as reasons for nonadherence.…”
Section: Available Self-report Adherence Measuresmentioning
confidence: 99%
“…Because these were healthy volunteers without any known deficits of visual or motor impairment, they were assumed capable of applying the ointment correctly at home, simulating the normal situation when dermatology patients apply topical therapies. We did not use the finger-tip principle of topical application and we did not include electronic surveillance such as medication event monitoring systems (MEMS), which may be difficult to adapt to topical formulations as the system was originally designed for oral products (9,10). In fact, the quantity of study medicine each day would likely have been shown to vary even more if we had used MEMS.…”
Section: Discussionmentioning
confidence: 98%